Immunological and nutritional perspectives on macromolecular therapies for thoracic tumors - Rong, Hao; Zheng, Min; Qi, YunXiang; Ma, Ke (Frontiers in Immunology, 2025)
Thoracic tumors have high incidence and mortality rates, and present poor prognosis due to the limited efficacy of traditional therapies. Macromolecular drugs such as monoclonal antibodies and antibody-drug conjugates (ADCs) have shown promise for the treatment of lung cancer, breast cancer, and esophageal cancer. Different combinations of immunotherapy, chemotherapy, and targeted therapy have significantly improved the survival indicators of patients with thoracic tumors. Nevertheless, these combination treatment regimens have safety issues such as immune-related adverse reactions and hematological toxicity. The development of novel macromolecular drugs also faces challenges related to optimizing the affinity of antibodies, and improving the design of linkers and delivery carriers. Furthermore, the clinical application of these drugs is restricted by tumor heterogeneity, drug resistance, and exorbitant prices, along with ethical concerns and difficulties in obtaining in regulatory approval. However, macromolecular drugs present significant potential in technological innovation, combination therapy, and personalized treatment, which is expected to drive market development, improve patients’ quality of life, and reduce the socioeconomic burden of cancer. This review focuses on the application of novel macromolecular drugs for the treatment of thoracic tumors, with the aim of providing a reference for further research and clinical translation.